2005
DOI: 10.1002/j.2050-0416.2005.tb00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Hydrostatic Pressure-Temperature Combinations on the Activity of β-Glucanase from Barley Malt

Abstract: J. Inst. Brew. 111(3), 282-289, 2005␤-Glucanase from barley malt is known to be thermolabile but important in the mashing process. Therefore, the potential of increasing the thermostability of ␤-glucanase in ACES buffer (0.1 M, pH 5.6) by high hydrostatic pressure has been investtigated. Inactivation of the enzyme as well as changes of the conversion rate in response to combined pressure-temperature treatments in the range of 0.1-900 MPa and 30-75°C were assessed by analyzing the kinetic rate constants. A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…Such antagonistic effect of pressure and temperature was observed throughout the low pressure/high temperature (100-400 MPa; N60°C) range investigated. This phenomenon of pressure induced stabilisation of PPO and other enzymes has often been reported in literature (Ludikhuyze, Van Loey, Indrawati, Denys, & Hendrickx, 2002;Buckow, Heinz, & Knorr, 2005) and takes place, when the volume difference between folded and unfolded proteins will be positive. This might be due to the strengthening of hydrophobic interactions and enhanced formation of hydrogen bonds under high pressures leading to a more compact, rigid molecular structure reducing the thermal fluctuations caused by high temperatures (Balny & Masson, 1993;Gross & Jaenicke, 1994;Mozhaev, Lange, Kudryashova, & Balny, 1996;Boonyaratanakornkit, Park, & Clark, 2002).…”
Section: Combined Thermal and High Pressure Treatment Of Ppo In Applementioning
confidence: 90%
“…Such antagonistic effect of pressure and temperature was observed throughout the low pressure/high temperature (100-400 MPa; N60°C) range investigated. This phenomenon of pressure induced stabilisation of PPO and other enzymes has often been reported in literature (Ludikhuyze, Van Loey, Indrawati, Denys, & Hendrickx, 2002;Buckow, Heinz, & Knorr, 2005) and takes place, when the volume difference between folded and unfolded proteins will be positive. This might be due to the strengthening of hydrophobic interactions and enhanced formation of hydrogen bonds under high pressures leading to a more compact, rigid molecular structure reducing the thermal fluctuations caused by high temperatures (Balny & Masson, 1993;Gross & Jaenicke, 1994;Mozhaev, Lange, Kudryashova, & Balny, 1996;Boonyaratanakornkit, Park, & Clark, 2002).…”
Section: Combined Thermal and High Pressure Treatment Of Ppo In Applementioning
confidence: 90%
“…Such antagonistic effect of pressure was observed throughout the low pressure/high temperature (> 658C) range investigated. This phenomenon of pressure-induced stabilization of enzymes and other proteins against thermal denaturation has often been encountered in pressure-assisted enzyme inactivation (Buckow et al, 2005a;Ludikhuyze et al, 2002), and is possibly explained by the strengthening of hydrophobic interactions and intramolecular hydrogen bonds formation (Balny and Masson, 1993;Mozhaev et al, 1996). Water molecules also exert a profound influence on protein stability through hydration of the amino acids.…”
Section: Effect Of Calcium On Enzyme Stabilitymentioning
confidence: 97%
“…Previous studies (Buckow et al, 2005a;Heinz et al, 2005) revealed that combined thermal and pressure inactivation of enzymes which have more than one catalytic isoforms can simply be described by a nth-order reaction, expressing the residual enzyme activity (A) as a function of time while pressure and temperature remains constant:…”
Section: Kinetic Data Analysis and Modelingmentioning
confidence: 99%
“…This type of processing can cause changes in interactions inter and intra-molecular, which can induce conformational changes in macromolecules. In this way the reversible and irreversible denaturation of proteins occurs (Heremans and Smeller, 1998) as well as the enzymatic activation (Asaka et al, 1993) and inactivation (Hendrickx et al, 1998;Buckow et al, 2005). This process is isostatic, i.e., the pressure is transmitted evenly and instantly, and adiabatically, which means that the shape or the size of the food does not matter (Wilson et al, 2008).…”
Section: Thermal Treatment: Pasteurizationmentioning
confidence: 99%